Pengaruh Kompetensi, Rotasi Kerja Dan Pengembangan Karir Terhadap Kinerja Pegawai Pada Dinas Syariat Islam Provinsi Aceh - Muhammad Riski; Lukman T. Ibrahim; Isthafan Najmi (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Human resources are one of the important factors in a company to achieve its goals and objectives, because human resources are one of the determining factors for the success or failure of a company in achieving its goals. The aim of this research is to determine the magnitude of the influence of competency, work rotation and career development on employee performance at the Aceh Province Islamic Sharia Service. This research uses a quantitative approach using primary data through questionnaires. In this research, the population was 54 employees in the Aceh Province Islamic Sharia Service, so the sample used was a population sample. The sampling method in this research is using a census model. Based on the results of the t test (partial) regarding the competency variable, the value tcount>ttable (2.891>2.008), with a significant value of 0.000 <0.05. The results of the t test (partial) regarding the work rotation variable show that the value tcount>ttable (2.325>2.008), with a significant value of 0.000 <0.05, then the results of the ttest (partial) regarding the career development variable show that the value tcount>ttable (3.242>2.008 ), with a significant value of 0.000 < 0.05, then Ha is accepted, meaning vari. The results of the f test (simultaneous) conclude that the value of Fcount>Ftable or equal to (7.237>2.790), with a significant value of 0.000 <0.05, then Ha is accepted. This means that Competency, Job Rotation and Career Development simultaneously have a significant effect on employee performance at the Aceh Province Islamic Sharia Service.